MICRO-SATELLITE DNA ASSOCIATE WITH DISEASES AND CANCERS - Hozan I. Ibrahim Rwandzy; Hazha Jamal Hidayat Hazha Jamal Hidayat; Seerwan Hamadameen Sulaiman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Most of the human genome is comprised of non-coding DNA. Satellite DNA (satDNA) is a non-coding region, and it is one of the DNA types that contains repeated sequences. Microsatellite (MS) DNA is one of the satDNAs. MS has a tiny percentage of satellite DNA, and several repeat sequences of it have been identified as significant participants in genome structure. MS is correlated with frequent mutations, epigenetic alterations, and changes in gene expression. MS may significantly affect phenotypes. Many genetic diseases and cancer forms have microsatellite instability, which is a significant feature. The context of disease-focused research for many types of mental disabilities has shifted because of the revelation that the expansion of unstable repeats can induce a range of neurological diseases and cancers. This review’s goal is to summarize how MS affects humans through genetic disorders, neurological diseases, developmental disorders, and cancers.